Crossover of the relative heat transport contributions of plume ejecting and impacting zones in turbulent Rayleigh-Bénard convection(a)Contribution to the Focus Issue Turbulent Thermal Convection edited by Mahendra Verma and Jörg Schumacher. (16th July 2021) - Reiter, Philipp; Shishkina, Olga; Lohse, Detlef; Krug, Dominik
Abstract: Turbulent thermal convection is characterized by the formation of large-scale structures and strong spatial inhomogeneity. This work addresses the relative heat transport contributions of the large-scale plume ejecting vs . plume impacting zones in turbulent Rayleigh-Bénard convection. Based on direct numerical simulations of the two dimensional (2-D) problem, we show the existence of a crossover in the wall heat transport from initially impacting dominated to ultimately ejecting dominated at . This is consistent with the trends observed in 3-D convection at lower Ra, and we therefore expect a similar crossover to also occur there. We identify the development of a turbulent mixing zone, connected to thermal plume emission, as the primary mechanism for the takeover. The mixing zone gradually extends vertically and horizontally, therefore becoming more and more dominant for the overall heat transfer.